Transmission of entomopathogenic fungi on banana weevil control Transmissão de fungo entomopatogênico no controle da broca do rizoma - Ernesto Antonio Lema López (Semina: Ciências Agrárias, 2012)
The aim of this study was to assess the transmission of the entomopathogenic fungus Beauveria bassiana among adults of banana weevil (Cosmopolites sordidus) in the field. C. sordidus healthy adults were marked and released on the basis of banana plants. Two days later insects marked and inoculated with the entomopathogenic fungus were released in the same area. Pseudostem traps were placed at 7, 14, 21 and 28 days for recover of released insects and to evaluate the mortality. It was observed that 3.7% of the non inoculated insects died due to pathogen infection caracterizing B. bassiana transmission between inoculated and healthy insects due to an increase in natural pre-existing prevalescence that was 0.3% of infected insects. O objetivo deste trabalho foi avaliar a transmissão do fungo entomopatogênico (Beauveria bassiana) entre adultos da broca do rizoma (Cosmopolites sordidus) em condições de campo. Insetos adultos e sadios de C. sordidus foram marcados e liberados na base de touceiras de bananeiras e dois dias após na mesma área foram liberados insetos marcados e inoculados com o fungo B. bassiana. Aos 7, 14, 21 e 28 dias armadilhas de pseudocaule foram utilizadas para a recaptura dos insetos e determinação da mortalidade pelo fungo. Observou-se uma porcentagem de infecção de 3,7% dos insetos sadios recuperados, caracterizando a transmissão de B. bassiana entre insetos inoculados e sadios devido ao aumento da prevalência natural preexistente que era de 0,3 % de insetos doentes.